The Implementation of Task and Student's Response at The Tenth Grade of Senior High School in Prawira Marta, Kartasura. - Kurniawati, Yulia, Drs. Djoko Srijono, M.Hum, Mauly Halwat Hikmat, Ph.D (2017)
This research aims at1) Describing the kind of task used by English teacher at Senior High School in Prawira Marta, Kartasura, 2) Describing the procedures of English teacher on giving task, 3) Describing student responses from the task that was got and 4) Classifing the difficulties on giving the task. In this research, the researcher uses a descriptive qualitative as the type of the research. The object of the study focuses on implementation of task and student's responses at Senior High School especially in the tenth Accounting Department grade in Prawira Marta, Kartasura. The data source of this research is English teacher and the student of Accounting Department grade at Senior High school in Prawira Marta, Kartasura, field note, syllabus, textbook, worksheet, and lesson plan. The technique for analyzing data is 1) Collecting the data taken from observation, interview, documentation and questionnaire. 2) The collected data are analyzed by reducing, displaying and conclusion drawing/verification data. Based on the research finding, it was found that 1) There are two kinds of task used by English teacher namely individual and group task. Individual task includes homework that divided into two kinds namely, practice and preparation homework. Group task include game, problem solving, and discussion. 2) Procedures for giving task starts from pre-task, cycle/during task and post-task. 3) Student's response to the task is positive and satisfied. 4) Difficulties on giving task are faced because student ability in vocabulary and student's focus on the teacher are limited.